Japan in the world : Shidehara Kijūrō, pacifism, and the abolition of war. - Schlichtmann, Klaus, 1944- (AsiaWorld., 2009)
The twentieth century is as remarkable for its world wars as it is for its efforts to outlaw war in international and constitutional law and politics. Japan in the World examines some of these efforts through the life and work of Shidehara Kijuro, who was active as diplomat and statesman between 1896 until his death in 1951. Shidehara is seen as a guiding thread running through the first five decades of the twentieth century. Through the 1920s until the beginning of the 1930s, his foreign policy shaped Japan's place within the community of nations. The positive role Japan played in internation.